New Zealand : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
After several years of strong growth, the New Zealand economy entered a recession in early 2008. The 2009 Article IV Consultation highlights that the near-term outlook for New Zealand is weak. Executive Directors have noted that the significant fiscal stimulus under way will help cushion the near-term impact of the downturn. They have also commended the authorities for taking timely measures to strengthen confidence and support bank access to funding, including through the introduction of funding guarantees and the expansion of the Reserve Bank's liquidity facilities and acceptable collateral instruments.